Validity and reliability study of the pediatric Rome III questionnaire for Turkish children and adolescents - Özgenç, Funda; Akaslan Kara, Aybüke; Demiral Yılmaz, Nilüfer; Önen, Şerife Şebnem; Ögretmen, Tuncay; Ecevit, Çiğdem Ömür; Çalışkan, Süleyman Ayhan (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Questionnaire on Pediatric Gastrointestinal Symptoms: Rome III version (QPGS-RIII), originally developed in English, was adapted to different languages in order to widen its use. The aim of this study was to evaluate the validity and reliability of a questionnaire on the Pediatric QPGS-RIII parent-report form for children and self-report form for children and adolescents, which has been adapted into Turkish. Materials and Methods: The study group comprised 7–18-year-old children/adolescents (n=690) who presented to Ege University School of Medicine, Department of Child Health and Diseases outpatient clinic. In the study, the validity and reliability of the QPGS-RIII Turkish version of the questionnaire was established. Results: Confirmatory factor analysis (CFA) resulted in a 10-factor model satisfactory construct for the validity and in acceptable indices of goodness of fit. Standardized coefficients determined with CFA in the Turkish version of the instrument ranged between 0.15 and 0.87 in the 7–9-year-old children and between 0.13 and 0.98 in the 10–18-year-old children/adolescents. t-values of all the factor loadings were significant. In addition, the test-retest analyses were above 0.70, except for the abdominal migraine factor. Conclusion: Findings relating to the validity and reliability of the study indicated that the Turkish version of the instrument could be adequately used to assess functional gastrointestinal disorders (FGIDs) in Turkish children and adolescents. The Turkish version of the instrument is therefore recommended to be used in epidemiologic studies and in clinical trials to be conducted in a Turkish-speaking population.